Translation Strategy Analysis of the Poem “Invictus” by William Ernest Henley : Analisis Strategi Penerjemahan pada Puisi “Invictus” Karya William Ernest Henley - Rusdiana, Vianita; Faiz Akbar Leksananda (Kementerian Sekretariat Negara Republik Indonesia, 2025)
This article discusses the translation strategy of English literature of poetry entitled “Invictus” by William Ernest Henley published in 1888, translated into Indonesian by Renny Novita in her writing post on Renov Rainbow’s website. This research aims to identify the translation strategies used in translate of the poem “Invictus”. The methods used in this research is descriptive qualitative. Based on the data, 17 lines of the poem were analyzed to determine the translation strategies used in translating the poem. The result of the data analyzed refers to the theoretical basis of translation strategies by Suryawinata & Haryanto (2016), 8 data were found using semantic strategies; synonyms (47.06%, 3 data using structural strategies; reduction (17.65%), 2 data using structural strategies; transposition (11.76%), 3 data using semantic strategies; modulation (17.65%), and 1 data using pragmatic strategies; changing clarity of meaning (5.88%). Among the translation strategies used, the most common one is the semantic strategy and synonym.